Obstetric Considerations in a Rare Cardiovascular Catastrophe Needing Multidisciplinary Care - Neeta Singh; Debjyoti Karmakar; V. Devagorou; Rajnish Tiwari; Sunesh Kumar (Case Reports in Vascular Medicine)
Cardiovascular emergencies especially aortic dissections are rare in pregnancy. We report a case of Stanford Type A aortic dissection at 33 weeks of pregnancy presenting in shock. Rapid multidisciplinary approach and special obstetric considerations led to a successful outcome in this case.